2019
DOI: 10.1021/acs.est.9b00665
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Activity over the Submonolayer MoO3 Motif on TiO2 for Nitrogen Oxide Emission Abatement

Abstract: Surface restructuring is a useful approach to modulating the properties of nanoparticles. A low-dimensional atomic-thickness active species may exhibit remarkably enhanced activity, in contrast to the inert nature of its bulk counterparts. Here, we report a procedure for growing in situ a low-dimensional monolayer-thick MoO 3 entity from its bulk precursor. Traditional analysis of NO abatement catalyzed by vanadium-based materials implicates vanadium as the active site enhanced by the promoter element W or Mo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…Fe 2 O 3 /MoO 3 /TiO 2 shows irregular, rough shapes and has a large size variation (see the SEM image in Figure S1). The submonolayer structured MoO 3 on TiO 2 has been evidenced by our previous work . However, when MoO 3 /TiO 2 was mixed with Fe 2 O 3 , it was difficult to distinguish the MoO 3 surface layer by TEM because of the strong signals from Fe 2 O 3 and TiO 2 .…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Fe 2 O 3 /MoO 3 /TiO 2 shows irregular, rough shapes and has a large size variation (see the SEM image in Figure S1). The submonolayer structured MoO 3 on TiO 2 has been evidenced by our previous work . However, when MoO 3 /TiO 2 was mixed with Fe 2 O 3 , it was difficult to distinguish the MoO 3 surface layer by TEM because of the strong signals from Fe 2 O 3 and TiO 2 .…”
Section: Resultsmentioning
confidence: 55%
“…The origin of the extremely high resistance to Na 2 SO 4 is elucidated. Recently, we have shown that MoO 3 with a layered structure has important implications in catalysis . Moreover, the intercalation of Na + ions into MoO 3 is expected, according to the report of a previous study .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…3b, only a peak at ∼1600 cm −1 assigned to the adsorbed gas NH 3 on Lewis sites appears in the spectrum of TiO 2 . 29 However, when single Mo atoms were anchored on TiO 2 , significant signals at ∼1670 and ∼1455 cm −1 appeared, manifesting the increased NH 3 coordination of Brønsted sites in the form of NH 4 + , 29,38 i.e. , Mo–O–H structures were formed on the surface of Mo 1 /TiO 2 , which are totally different from that in bulk MoO 3 where no relevant peak was observed.…”
Section: Resultsmentioning
confidence: 94%
“…27,28 Hence, a catalyst with Mo–Ti acid–base dual sites should readily adsorb NH 4 + and HSO 4 − , respectively. Moreover, owing to the unsaturated coordination configuration, the surface Mo ions often have the desired ability to facilitate the oxidation of NH 4 + , 29 generating reduced Mo species. Due to the charge transfer between Mo and Ti atoms via Mo 5+ + Ti 4+ → Mo 6+ + Ti 3+ , 30 the produced Ti 3+ , which often has a higher electron state density near the Fermi level ( E f ), 31 favourably accelerates the reduction of HSO 4 − .…”
Section: Introductionmentioning
confidence: 99%